2020
DOI: 10.1109/access.2020.3038559
|View full text |Cite
|
Sign up to set email alerts
|

Timing Predictability in High-Performance Computing With Probabilistic Real-Time

Abstract: Application requirements in High-Performance Computing (HPC) are becoming increasingly exacting, and the demand for computational resources is rising. In parallel, new application domains are emerging, as well as additional requirements, such as meeting real-time constraints. This requirement, typical of embedded systems, is difficult to guarantee when dealing with HPC infrastructures, due to the intrinsic complexity of the system. Traditional embedded systems static analyses to estimate the Worst-Case Executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, the EVT hypotheses must be satisfied. First preliminary results [13] showed that the EVT hypotheses could be satisfied with due safety technical shrewdness. The presence of heterogeneous hardware (such as GPGPU computing), which is exploding in HPC in the last years, exhibited an improvement in compliance of EVT hypotheses compared to a full-homogeneous scenario.…”
Section: High-performance Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the EVT hypotheses must be satisfied. First preliminary results [13] showed that the EVT hypotheses could be satisfied with due safety technical shrewdness. The presence of heterogeneous hardware (such as GPGPU computing), which is exploding in HPC in the last years, exhibited an improvement in compliance of EVT hypotheses compared to a full-homogeneous scenario.…”
Section: High-performance Computingmentioning
confidence: 99%
“…What is the relation with embedded safety-critical systems we are talking about in this chapter? Because time-critical applications are also emerging on these systems [13], such as medical imaging, natural disaster prediction, or structures monitoring. All of these application categories require a large amount of computational power (consequently the need to run on HPC clusters) and timing guarantees on the results.…”
Section: High-performance Computingmentioning
confidence: 99%
“…The problem of estimating a safe and tight Worst-Case Execution Time (WCET) in modern processors is an open problem and key issue of real-time embedded systems, and, for certain applications, of HPC computing nodes [26]. The increasing complexity of modern computing platforms (many cores, advanced pipelines, multi-level caches, heterogeneity, etc.)…”
Section: Real-time Properties Assessment and Enforcementmentioning
confidence: 99%
“…In addition, by integrating the programming model with the resource management layers we could dynamically tune the numerical accuracy (precision) of the algorithms' implementation, with respect to the actual application requirements and power/energy constraints [62]. Similarly, this applies to the problem of guarantee real-time requirements to time-critical applications [61,63]. In general, given the reference hardware platform and the application use-cases, the TEXTAROSSA project would represent an extremely interesting testbench for exploring novel power and energy management strategies, by operating at both software and hardware level.…”
Section: Runtime Services: Energy/power Managementmentioning
confidence: 99%